1999
DOI: 10.3354/dao036201
|View full text |Cite
|
Sign up to set email alerts
|

Ichthyophthiriasis in carp Cyprinus carpio:infectivity of trophonts prematurely exiting both the immune and non-immune host

Abstract: Ichthyophthirius multifihis exposed to naturally immunised carp established short-term infections, the majority of parasites actively emerging within 2 h of entering the epidermis. A small, but significant, number of these expelled parasites were shown to retain theront-like properties with the capacity to directly re-invade a further fish host. Infectivity fell rapidly with time in the host and was comparable to that of trophonts of a similar age artificially induced to emerge from non-immune hosts with the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Cross-binding of these proteins by antibodies causes the parasites to prematurely exit an immune host [8], [20], [21]. This makes the I-ags potential vaccine candidates and some immunization trials have confirmed their potential as efficient inducers of immunity [22][24].…”
Section: Introductionmentioning
confidence: 99%
“…Cross-binding of these proteins by antibodies causes the parasites to prematurely exit an immune host [8], [20], [21]. This makes the I-ags potential vaccine candidates and some immunization trials have confirmed their potential as efficient inducers of immunity [22][24].…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism results in complete, or partial, resistance to infection, otherwise known as immunity. Recent studies have suggested that rather than killing the infective stages of I. multifiliis the parasites may be forced to exit the fish prematurely in response to antibody binding (Wahli & Matthews, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The i-antigen is a single polypeptide chain that -in combination with adjuvant -is a protective immunogen when administered i.p. Interestingly, Cross and Matthews (1992) and Wahli and Matthews (1999) found that immune responses following exposure to sublethal levels of live theronts do not seem to prevent theronts from penetrating into the epidermis of carp during subsequent challenge with a lethal level but promote exit of most trophonts within 2 h. These exited trophonts were still infective (Wahli and Matthews, 1999). Despite lymphopenia (Hines and Spira, 1973) both systemic and mucosal antibody production has been shown after infection, and antibodies seem to play a major role in protective immunity (Dickerson and Findly, 2014).…”
Section: Adaptive Immunitymentioning
confidence: 99%